Knowledge Building and Knowledge Forum: Getting Started With Pedagogy and Technology (LEARNing Landscapes, 2013)
Knowledge Building provides a model of education for a knowledge age—a model of collective responsibility for idea improvement. This article provides two examples of getting started with the pedagogy and the technology, one from Senior Kindergarten, with students working together to understand why leaves change color in the fall, and the other from Grade 1, featuring explorations of the water cycle. In addition to the classroom work that is reported, commentary on school practices from a Librarian-Technology coordinator and Vice Principal are included to provide a broader school perspective on the work presented in this article.
Keywords: pedagogy; technology; kindergarten; grade one; knowledge age; knowledge building